TANTANGAN MAUPUN PELUANG PENGELOLAAN WAKAF PRODUKTIF DI INDONESIA: Wakaf Produktif Di Indonesia - Restu Amin (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
Productive waqf is an Islamic financial instrument that has great potential in supporting economic and social development in Indonesia. This article explores various challenges and opportunities in managing productive waqf, which include a lack of community understanding, limited nazhir capacity, and regulations that are not yet fully supportive. On the other hand, big opportunities are seen in increasing public awareness, the potential of the digital economy, and collaboration between stakeholders. With a strategic approach, such as waqf literacy education, strengthening nazhir capacity, optimizing digital technology, and supporting regulations, productive waqf can be maximized as an instrument for economic empowerment of the people. This research uses descriptive qualitative research with a literature study approach. The literature study was carried out by collecting data and information from various trusted sources, such as books, scientific journals, previous research articles, and relevant digital sources. These data were then analyzed critically to provide a comprehensive picture of the problems raised. The research results show that productive waqf can be a strategic solution to overcome the problems of poverty, unemployment, and economic inequality. This research aims to provide a comprehensive view for the development of productive waqf as a pillar of an inclusive and sustainable Islamic economy. The conclusion from this panel is that productive waqf management in Indonesia has enormous potential to support the social and economic development of the people. With the largest Muslim population in the world, Indonesia has abundant waqf assets, including land, buildings and cash.